your answer is B=17
hope I helped you
Answer:
The number (√5 + 2)(√5 - 2) can be simplified using the difference of squares formula, which states that (a + b)(a - b) = a² - b². In this case:
(√5 + 2)(√5 - 2) = (√5)² - 2² = 5 - 4 = 1
So, the number (√5 + 2)(√5 - 2) is equal to 1, which is a rational number because it can be expressed as a ratio of two integers (1/1). Therefore, the correct answer is:
b. a rational number
The expression ( √5 +2)(√5 - 2) can be simplified using the difference of squares formula. The result is a rationalnumber, making option b. a rational number the correct answer.
The expression ( √5 +2)(√5 - 2) can be simplified using the difference of squares formula. The difference of squares formula states that a^2 - b^2 = (a + b)(a - b). In this case, a = √5 and b = 2. Plugging these values into the formula, we have (√5)^2 - 2^2 = ( √5 +2)(√5 - 2) = 5 - 4 = 1.
Since 1 is a rational number (it can be expressed as a fraction), the correct answer is b. a rational number.
#SPJ11
Answer: There is 61.9% decrease in the value from 126 ounces to 48 ounces.
Step-by-step explanation:
Original value=126 ounces
New value = 48 ounces
Difference = 126-48 = 78 ounces
So, Percentage of decrease value is given by
So , there is 61.9% decrease in the value from 126 ounces to 48 ounces.
Answer:
Decrease in percentage = 61.9%
Step-by-step explanation:
Decrease from 126 ounces to 48 ounces percent
First find out the amount of decrease. Subtract the number to find the amount of decrease
now find out which percentage is 78
percentage =
Decrease in percentage = 61.9%
With step by step explanation !
It's easier to deal with the symbolic sum (in sigma notation),
Expanding the terms in the fraction, computing the quotient, and decomposing into partial fractions gives
and it's the latter two terms that reveal a telescoping pattern.
In case you need more details about the partial fraction decomposition, we are looking for coefficients a and b such that
or
which gives a = 1, and a + b = 0 so that b = -1.
Our sum has been rearranged as
The remaining telescoping sum is
1/2 [(1/1 - 1/2) + (1/2- 1/3) + (1/3- 1/4) + … + (1/48- 1/49) + (1/49- 1/50) + (1/50 - 1/51)]
and you can see how there are pairs of numbers that cancel, so that the sum reduces to
1/2 [1/1 - 1/51] = 1/2 [1 - 1/51] = 1/2 × 50/51 = 25/51
So, our original sum ends up being
x - 3y for y
Answer:y=x/3
Step-by-step explanation:
x-3y=0
or,x=3y
y=x/3
He miscalculated the size of the earth and thought he had reached Asia.
B.
He thought the language of the people he met was Chinese and didn't realize he was in the Americas.
C.
He did not bring enough supplies, so he had to stop in the Americas instead of going all the way to Asia.
D.
He did not realize how bad storms could be and got so far off course that he reached the Americas instead of Asia.
I will give brainliest if it’s correct
when we multiply two values in scientific notation with the same base,their powers get added .